Implementasi Blended Learning pada Perkuliahan Prodi Pendidikan Agama Islam di UIN Walisongo Semarang - Diva Aulia Budianto; Nur Rohma Zulika; Bakti Fatwa Anbiya (Yayasan Pendidikan Penelitian Pengabdian Algero, 2023)
21st-century education utilizes Information and Communication Technology (ICT) as a learning medium by starting to reduce the use of old methods to keep abreast of the current development. Daring is a form of utilizing ICT technology in education through the use of online features as learning intermediaries. But in reality, daring doesn’t provide effectiveness because it causes learning problems. Therefore, Blended Learning is considered to be a method that can solve daring problems. Blended learning is a combination of daring and luring. UIN Walisongo Semarang is a university that applies blended learning. This is motivated by the emergence of daring problems during COVID-19. This research approach uses a qualitative approach with descriptive analysis methods. Data collection techniques are interviews and documentation. This study focuses on the role of implementing blended learning at UIN Walisongo Semarang in overcoming daring problems. The result of this study is the application of blended learning at UIN Walisongo during COVID-19 is good enough and effective enough to overcome problems arising from daring during COVID-19. But blended learning is not recommended to be applied continuously because can make students confuse, but blended learning can be done occasionally when teachers/lecturers are unable to be physically present in class.